Insights on Distinct Left Atrial Remodeling Between Atrial Fibrillation and Heart Failure With Preserved Ejection Fraction - Kuo, Jen-Yuan; Jin, Xuanyi; Sun, Jing-Yi; Chang, Sheng-Hsiung; Chi, Po-Ching; Sung, Kuo-Tzu; Mok, Greta S. P.; Yun, Chun-Ho; Chang, Shun-Chuan; Chung, Fa-Po; Yu, Ching-Hsiang; Wu, Tung-Hsin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Heart failure with preserved ejection fraction (HFpEF) and atrial fibrillation (AF) commonly coexist with overlapping pathophysiology like left atrial (LA) remodeling, which might differ given different underlying mechanisms. Objectives: We sought to investigate the different patterns of LA wall remodeling in AF versus HFpEF. Methods: We compared LA wall characteristics including wall volume (LAWV), wall thickness (LAWT), and wall thickness heterogeneity (LAWT[SD]) and LA structure, function among the controls (without AF or HFpEF, n=115), HFpEF alone (n=59), AF alone (n=37), and HFpEF+AF (n=38) groups using multi-detector computed tomography and echocardiography. Results: LA wall remodeling was most predominant and peak atrial longitudinal strain (PALS) was worst in HFpEF+AF patients as compared to the rest. Despite lower E/e’(9.8±3.8 versus 13.4±6.4) yet comparable LA volume, LAWT and PALS in AF alone versus HFpEF alone, LAWV (12.6 [11.6–15.3] versus 12.0 [10.2–13.7]; p=0.01) and LAWT(SD) (0.68 [0.61–0.71] versus 0.60 [0.56–0.65]; p<0.001) were significantly greater in AF alone versus HFpEF alone even after multi-variate adjustment and propensity matching. After excluding the HFpEF+AF group, both LAWV and LAWT[SD] provided incremental values when added to PALS or LAVi (all p for net reclassification improvement <0.05) in discriminating AF alone, with LAWT[SD] yielding the largest C-statistic (0.78, 95% CI: 0.70–0.86) among all LA wall indices. Conclusions: Despite a similar extent of LA enlargement and dysfunction in HFpEF versus AF alone, larger LAWV and LAWT[SD] can distinguish AF from HFpEF alone, suggesting the distinct underlying pathophysiological mechanism of LA remodeling in AF versus HFpEF.